2013
DOI: 10.1364/boe.4.000917
|View full text |Cite
|
Sign up to set email alerts
|

Talbot-defocus multiscan tomography using the synchrotron X-ray microscope to study the lacuno-canalicular network in mouse bone

Abstract: The three-dimensional network of lacunae and canaliculi that regulates metabolism in bone contains osteocytes and their dendritic processes. We constructed a synchrotron radiation X-ray microscope for sequential tomography of mouse tibia first by using a Talbot interferometer to detect the degree of bone mineralization and then by using absorption contrast under a slightly defocused setting to enhance outline contrast thereby visualizing structures of the osteocyte lacuno-canalicular network. The resultant pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Serial section scanning electron microscopy also provides submicron resolution but has only been applied to demineralized tissues so far. The degree of mineralization in the vicinity of the LCN in mice bone has recently been shown to be accessible using an X‐ray microscope with a pixel size of 208 nm . Recently, we demonstrated that synchrotron phase nano‐computed tomography (SR‐PNCT) allows the 3D imaging of mass density with an isotropic voxel size ranging down to 60 nm in a field of view larger than 100 × 100 × 100 µm 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serial section scanning electron microscopy also provides submicron resolution but has only been applied to demineralized tissues so far. The degree of mineralization in the vicinity of the LCN in mice bone has recently been shown to be accessible using an X‐ray microscope with a pixel size of 208 nm . Recently, we demonstrated that synchrotron phase nano‐computed tomography (SR‐PNCT) allows the 3D imaging of mass density with an isotropic voxel size ranging down to 60 nm in a field of view larger than 100 × 100 × 100 µm 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The degree of mineralization in the vicinity of the LCN in mice bone has recently been shown to be accessible using an X-ray microscope with a pixel size of 208 nm. (21) Recently, we demonstrated that synchrotron phase nano-computed tomography (SR-PNCT) allows the 3D imaging of mass density with an isotropic voxel size ranging down to 60 nm in a field of view larger than 100 Â 100 Â 100 mm 3 . (22,23) In comparison to conventional attenuation tomography, phase imaging is more sensitive to changes in mass density by several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…We have been developing an approach where an X-ray imaging microscope is combined with a Talbot interferometer [69,70], as shown in Figure 8a. In the X-ray region, a Fresnel zone plate (FZP) is employed as a lens element.…”
Section: X-ray Phase Microscopy and Tomographymentioning
confidence: 99%
“…Thanks to the magnification of the microscope, a spatial resolution beyond the grating periods of G1 and G2 is achieved (200 nm in 2D and 600 nm in 3D [71]). This microscope was applied to mouse bone imaging [70][71][72][73] (Figure 9), which was conducted to study postnatal bone formation utilizing the advantage that the degree of bone mineralization and soft tissues (bone cells and blood vessels) are depicted together. Figure 8b shows another configuration for microscopic phase imaging, which has a potential for better image quality.…”
Section: X-ray Phase Microscopy and Tomographymentioning
confidence: 99%
“…However, the long scan times and small FOVs restrict applications. Recently, a Talbot interferometer for phase CT imaging and edge-enhanced absorption CT were combined at SPring-8 in Japan to image the LCN in mouse bone [72]. Nevertheless, the complex acquisition procedure and long acquisition time hampers the practicality of the approach.…”
Section: X-ray Ct Imaging Of Canaliculimentioning
confidence: 99%